Relationship between structural and dielectric properties of Zn-substituted Ba5CaTi2−xZnxNb8O30 tetragonal tungsten bronze. Issue 1 (21st November 2020) - Bendahhou, Amine; Marchet, Pascal; El-Houssaine, Ablouh; El Barkany, Soufian; Abou-Salama, Mohamed
Abstract : Ba5 CaTi2− x Zn x Nb8 O30 ceramics ( x = 0, 0.04, and 0.08) were synthesized by a conventional solid-state reaction method at 1300 °C for 6 hours. Abstract : Ba5 CaTi2− x Zn x Nb8 O30 ceramics ( x = 0, 0.04, and 0.08) were synthesized by a conventional solid-state reaction method at 1300 °C for 6 hours. The effects of the Ti/Zn ratio on structural and dielectric properties were studied by changing the value of x . The pure phase formation of all prepared Ba5 CaTi2− x Zn x Nb8 O30 compositions was confirmed by X-ray diffraction. The refinement of the (XRD) data by the Rietveld method confirmed the tetragonal crystal structure with the space group P 4 bm at room temperature. Scanning electron microscopy (SEM) showed that the Ba5 CaTi2− x Zn x Nb8 O30 ceramics have good sinterability, low porosity and uniform distribution of grains of unequal size over the entire surface in all the samples. The average grain size is in the range of 1.3 to 1.6 μm. The frequency-dependent dielectric properties were examined by complex impedance spectroscopy in the temperature range of 50 °C to 420 °C where a structural phase transition was observed for all the samples.